Tendencies of the International Labor Migration in the Conditions of Globalization of the Central Asian Region (Farabi Journal of Social Sciences, 2019)
Abstract. Article is devoted to the analysis of features, problems and factors of the international labor migration inthe countries of the Central Asia (CA) and development of recommendations about improvement of regulation of thisprocess in Kazakhstan. Article analyzes changes, tendencies and the directions of labor migration in the countries ofthe region. If at first these streams had a form of the compelled migration, further passed into scales of legal and illegallabor migration to such countries as Russia and Kazakhstan. Today the decrease in labor migration in these countriesconnected with devaluation of the Russian and Kazakhstan currency is noted. After all the factor of earnings movesworkers from Central Asia, and no changes in the labor and migratory legislation of the host country influence sostrongly migrants, as indicators of correction of currencies.